Exploration of central and peripheral neural properties in young and old humans - Guo, Yuxiao (2024)
Ageing is associated with declines of skeletal muscle mass and function attributable to neural adaptations at both central and peripheral levels. Voluntary movement is achieved via a complex interplay of motor cortex, spinal circuitry and motoneurons, which may be differentially influenced by the ageing process and sex-specific hormonal changes. However, there is limited data exploring age- and sex-related differences in neural inputs and individual motor unit properties in vastus lateralis, which appears to be highly susceptible to age-related functional impairment.